Address at the opening of the Forty-eighth Session. - Dodd, William H. (Statistical and Social Inquiry Society of Ireland, 1895)
The Society, as it now exists, is the combination of two societies, one for the investigation of statistics and the study of economic science, the other for the purpose of making social inquiries, mainly with a view to a reform of the laws that stand in the way of social progress. The earlier of the two societies was established in 1847, the other a few years later. They were amalgamated in 1851. I have endeavoured to fit myself for the duties which your kindness has called upon me to discharge, by a perusal of the transactions of the society, and it occurs to me that I cannot devote the time allotted to an opening address in any way more likely to be useful and interesting than by recalling your attention to the work of the society, and to some of the things that have happened since it was founded.
Read Tuesday, 20th November, 1894
Keywords: Ireland, 19th century; Social change; 314.15